2021
DOI: 10.25046/aj060109
|View full text |Cite
|
Sign up to set email alerts
|

Current Views on Issues and Technology Development in Forensic Accounting Education of Indonesia

Abstract: The objective of this study is to examine the current views of academics on issues and technology development in forensic accounting education. By applying the explanatory sequential mixed method, this study tries to acquire a better understanding of current perception regarding forensic accounting education. This study indicates that demand for forensic accounting services is expected to increase and offered as a separate courses at the graduate and undergraduate levels; respondent's perceived forensic accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Foreign Exchange Reserves and Imported Fuel and Engine Oil The study showed that foreign exchange reserves positively impact the volume of fuels and engine oil imports. According to (Chen et al, 2022;Tarjo et al, 2021) when Indonesia's foreign exchange reserves increase, the volume of imports will also increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foreign Exchange Reserves and Imported Fuel and Engine Oil The study showed that foreign exchange reserves positively impact the volume of fuels and engine oil imports. According to (Chen et al, 2022;Tarjo et al, 2021) when Indonesia's foreign exchange reserves increase, the volume of imports will also increase.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that foreign exchange reserves positively impact the volume of fuels and engine oil imports. According to (Chen et al, 2022;Tarjo et al, 2021) when Indonesia's foreign exchange reserves increase, the volume of imports will also increase. It is happened because Indonesia will be able to finance imports a lot when it has many foreign exchange reserves.…”
Section: Foreign Exchange Reserves and Imported Fuel And Engine Oilmentioning
confidence: 99%